A new species of Progomphus Selys, 1854 (Odonata: Anisoptera: Gomphidae) from Minas Gerais state, Southeastern Brazil - Vilela, Diogo Silva [UNESP]; Souza, Marcos Magalhes de (Magnolia Press, 2022)
Progomphus teolitavius sp. nov. (Odonata: Anisoptera: Gomphidae) is described and diagnosed based on a specimen collected in a gallery forest of Cerrado from Barroso municipality, Minas Gerais state, Brazil (-21.2238, -43.9895, 1033 m, 30.iii.2021, G.S. Santos leg.). The new species can be distinguished from congeners by its enlarged basal externo-lateral dilatation of cerci (which bears large teeth), and epiproct morphology.